Penerapan ChatGPT untuk Pemanfaatan Digitalisasi Informasi - Achmad Sarwandianto; Lusi Ariyani (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Kreo Village, located in Larangan District, Tangerang Regency, still relies heavily on very traditional communication methods in daily life. While this approach reflects local wisdom and strong cultural values, the changing times demand a digital transformation, especially in the field of communication. With the rapid advancement of digital technology and the growing quality of human resources in the village, the need for a more modern communication system is becoming increasingly important. One potential solution is the use of artificial intelligence technology such as ChatGPT. ChatGPT (Generative Pre-trained Transformer) is a language model based on AI developed by OpenAI. This technology can understand and generate natural language interactively, similar to human conversation. By integrating ChatGPT into community communication activities, Kreo Village can speed up access to information, facilitate the exchange of ideas and opinions, and bridge the existing digital gap. In addition, ChatGPT can also be used as an educational tool to help residents understand digital technology, support learning activities, and strengthen community participation in village development. Through this initiative, Kreo Village can move toward becoming a more inclusive, adaptive, and competitive digital village in the modern era.